Analisis Yuridis Permohonan Pailit PT. Bina Karya Sarana Oleh Kreditur (Studi Putusan No. 6/Pdt. Sus-Pailit/2018/PN.Niaga.Medan) - Ilham Rizki Hutabarat; Marsella Marsella; Sri Hidayani (Universitas Medan Area, 2022)
An application for bankruptcy is usually made on the grounds that neither he nor the business activities he carries out are able to carry out all of his obligations. In this case, the factors that cause bankruptcy are because the debtor is unable to pay his debts to one or more creditors whose due date for payment of debt repayments has fallen. The debtor's inability occurs because his debts are greater than his assets. This research uses a normative juridical law research method, the nature of the research is descriptive analytical with a literature study approach and a field study at the Medan Niaga District Court, then analyzed qualitatively. The responsibility of PT. Bina Karya Sarana against creditors who apply for bankruptcy is to pay all debts that exist on creditors with all debtor assets by law as collateral for debtor debts, all debtor assets are in general confiscation from the time the bankruptcy decision is pronounced. The judge's consideration in giving the bankruptcy decision on the decision no. 6/Pdt.Sus-Pailit/2018/ PN Niaga Medan, based on Law No. 37 of 2004 by examining the evidence provided by the applicant, and examining all legal facts that occurred during the trial process and, looking at the related elements Related articles contained in the lawsuit regarding the filing of bankruptcy in a limited liability company.